How to Generate a More Accurate Laboratory-Based International Normalized Ratio: Solutions to Obtaining or Verifying the Mean Normal Prothrombin Time and International Sensitivity Index - Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2019)
Although the landscape of anticoagulation therapy is evolving, vitamin K antagonists (VKAs) such as warfarin remain an anticoagulant of choice for many clinicians and their patients. Nevertheless, management of VKA therapy remains challenging, largely because of patient variability and drug and food interactions; thus, VKA dosing has to be personalized. This is achieved by regular monitoring using a test called the prothrombin time (PT), mathematically converted to an international normalized ratio (INR). The INR system is meant to harmonize laboratory test results by taking into account reagent and instrumentation variability that is otherwise expected to give rise to variable PT values, but which should accordingly lead to less variable INR values. Of clinical importance, too low an INR is suggestive of increased thrombotic risk and typically means the VKA dose should be increased, whereas too high an INR is suggestive of increased bleeding risk and typically means the VKA dose should be temporarily withheld and/or decreased. However, evidence continues to show that variability in INR values between laboratories remains unacceptably high. Given that modern instrumentation provides for robust analytical values—meaning highly reproducible intralaboratory clotting times or PTs in this case—the most likely cause of high INR variability is inconsistency in the INR test components—meaning the MNPT (mean normal PT) and ISI (international sensitivity index) values used by laboratories to generate a given INR. In other words, there are doubts as to the accuracy of some INR values because there are corresponding doubts about the accuracy of MNPT and/or ISI values that have been assigned by some laboratories for their reagent/instrument combination. The current report is intended to provide some solutions around the problems of inaccurate INRs, ISIs, and MNPTs, thus aiming to drive laboratory INRs closer to “truth,” and thus promote better patient management. The novel strategies include a primary process of transference to obtain/verify MNPT and/or ISI values for a new reagent using an existing reagent as reference, and a secondary process whereby external quality assessment data can be used to correct bias or existing errors in assigned MNPT and/or ISI values.
Keywords: international normalized ratio; mean normal prothrombin time; international sensitivity index